2011
DOI: 10.1175/jcli-d-10-05035.1
|View full text |Cite
|
Sign up to set email alerts
|

Warm Season Subseasonal Variability and Climate Extremes in the Northern Hemisphere: The Role of Stationary Rossby Waves

Abstract: This study examines the nature of boreal summer subseasonal atmospheric variability based on the new NASA Modern-Era Retrospective analysis for Research and Applications (MERRA) for the period 1979-2010. An analysis of the June, July and August subseasonal 250hPa v-wind anomalies shows distinct Rossby wave-like structures that appear to be guided by the mean jets.On monthly subseasonal time scales, the leading waves (the first 10 rotated empirical orthogonal functions or REOFs of the 250hPa v-wind) explain abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
171
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 35 publications
8
171
0
1
Order By: Relevance
“…Thus North American winter temperature is mostly controlled by these three atmospheric teleconnection patterns. It is noted that stationary Rossby waves, which play an important role in interannual variability of the teleconnections spanning from Eurasia to North America, are observed not only in winter but also in summer (e.g., Schubert et al 2011;Ding et al 2011;Wu et al 2009. Therefore, this study extends our previous analysis by characterizing the seasonality of the ABNA pattern.…”
Section: Introductionsupporting
confidence: 71%
“…Thus North American winter temperature is mostly controlled by these three atmospheric teleconnection patterns. It is noted that stationary Rossby waves, which play an important role in interannual variability of the teleconnections spanning from Eurasia to North America, are observed not only in winter but also in summer (e.g., Schubert et al 2011;Ding et al 2011;Wu et al 2009. Therefore, this study extends our previous analysis by characterizing the seasonality of the ABNA pattern.…”
Section: Introductionsupporting
confidence: 71%
“…In the meantime, several other unusually strong regional summer extremes already have occurred in recent years that make it questionable that only a purely stochastic mechanism of extremes is at work (8). The global observations attest that these extremes, such as the Russian heat wave in 2010 and the record heat wave in the United States in 2011, persisted over nearly the whole summer-which is not inherent in ordinary blockings with a characteristic e-folding time of about 5-7 d-and were in fact of hemispheric scale: a stable anomalous atmospheric circulation pattern enveloped the whole NH (4,(9)(10)(11)(12)(13)(14).…”
Section: T He Summer Of 2003 Was Highly Exceptional In the Northernmentioning
confidence: 99%
“…was subsequently applied to explain several important features of some of the recent summer extremes (18)(19)(20)(21)27 Petoukhov et al (34) proposed a common mechanism for generating persistent high-amplitude quasibarotropic planetaryscale wave patterns of the NH midlatitude atmospheric circulation with zonal wave numbers m = 6, 7, and 8 that can explain a number of the major NH summer extremes over the 1980-2011 period (34,35). Petoukhov et al (34) showed that these patterns could result from the trapping of free quasistationary barotropic Rossby waves with zonal wave numbers k equal or close to the three integer values indicated above, within the predominantly zonally oriented midlatitude waveguides.…”
Section: Significancementioning
confidence: 99%
“…However, a number of severe summer extremes have already occurred since then in the NH, particularly in Europe. The anomalous atmospheric circulation patterns accompanying these extremes were of hemispheric scale (14)(15)(16)(17)(18)(19)(20)(21)(22). They encircled the entire NH and persisted over nearly the whole summer, which is fundamentally different from conventional regional blocking events with about a 10-d life span (23).…”
mentioning
confidence: 94%